2010
DOI: 10.2116/analsci.26.117
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Investigation of Interactions between Potential DNA Targeted Compounds, 2,4-Di- and 2,3,4-Trisubstituted Benzimidazo[1,2-a]pyrimidines and Nucleic Acid

Abstract: The electrochemical aspects of interactions between DNA and two organic compounds are discussed herein. Potential DNA targeted compounds, 2-methyl-4-phenyl-benzo [4,5]imidazo[1,2-a]pyrimidine (c1) and 2,3,4-trimethyl-benzo[4,5]-imidazo[1,2-a]pyrimidine (c2), were synthesized and their cytotoxic and/or growth inhibitory effects were studied previously. Disposable sensor technology was used to explore the interaction between the compounds and nucleic acid, such as fish sperm DNA at the electrode surface and in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…It can be concluded that DTIC was more effectively interacted with ssDNA than dsDNA, due to obtained higher decrease % at both DTIC and guanine oxidation signals. The decrease at the guanine signal obtained after interaction process may be attributed to the DTIC alkylating structure, which was delivering methyl group to purine bases of DNA (O6‐guanine; N7‐guanine) .…”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that DTIC was more effectively interacted with ssDNA than dsDNA, due to obtained higher decrease % at both DTIC and guanine oxidation signals. The decrease at the guanine signal obtained after interaction process may be attributed to the DTIC alkylating structure, which was delivering methyl group to purine bases of DNA (O6‐guanine; N7‐guanine) .…”
Section: Resultsmentioning
confidence: 99%
“…This decrease in electrode response obtained after the interaction process was similar to the results in earlier reports related to DNA interaction of some anticancer drugs and DNA-targeted compounds. 14,25,26,35,36 It may be attributed to the intercalation of these Mannich bases into the base pairs of DNA. This phenomenon could be explained by the shielding of oxidizable groups of electroactive base guanine, 14,16.22 while the compounds can interact with the double helix of DNA at the electrode surface due to possible intercalation and/or alkylation mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, the benefit of the electrochemical recognition of the interaction between each Mannich base (C1/C2/C3/C4) and DNA has been shown for the first time herein using a faster, more sensitive, and less laborious voltammetric technique with the advantages of disposable PGE technology. 14,16,37 The success of the PGE over existing carbon electrodes is because it is commercially available, practical and cost-effective in use, and has better reproducibility. The electrochemical method presented here is experimentally convenient and sensitive, requiring only small amounts of DNA or compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Belonging to the structural features of both the molecule and DNA, several molecules indicate more than a single interaction mode with DNA. Intercalation is the most common way to link directly and selectively . Intercalating occurs when an aromatic ring of the drug is embedded among the base pairs in nucleic acid duplex, which enhances the distance amid the base pairs .…”
Section: Introductionmentioning
confidence: 99%